2009
DOI: 10.1007/s00425-009-0956-9
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced curcin-L promoter in leaves of Jatropha curcas L. and characterization in transgenic tobacco

Abstract: Ribosome-inactivating proteins (RIPs) represent a type of protein that universally inactivates the ribosome thus inhibiting protein biosynthesis. Curcin-L was a type I RIP found in Jatropha curcas L.. Its expression could be activated in leaves by treatments with abscisic acid, salicylic acid, polyethylene glycol, temperature 4, 45 degrees C and ultraviolet light. A 654 bp fragment of a 5' flanking region preceding the curcin-L gene, designated CP2, was cloned from the J. curcas genome and its expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…43,44 The activity of a curcin protein isoform against viral and fungal diseases has been proven by heterologous expression in tobacco; the expression of this curcin gene was induced by abiotic and biotic stresses in leaves. 4547 So far, Jatropha genes encoding three isoforms of curcin have been reported and deposited in public DNA databases. In our Jatropha genome sequence, only three contigs were identified to encode amino acid sequences highly similar to those coding for curcin, confirming that the Jatropha genome contains three curcin genes.…”
Section: Resultsmentioning
confidence: 99%
“…43,44 The activity of a curcin protein isoform against viral and fungal diseases has been proven by heterologous expression in tobacco; the expression of this curcin gene was induced by abiotic and biotic stresses in leaves. 4547 So far, Jatropha genes encoding three isoforms of curcin have been reported and deposited in public DNA databases. In our Jatropha genome sequence, only three contigs were identified to encode amino acid sequences highly similar to those coding for curcin, confirming that the Jatropha genome contains three curcin genes.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies report that RIPs may be involved in the plant defense response [5254]. Although RIPs have been classified into three groups, based on their structure and functions, type I RIPs are most important in J. curcas.…”
Section: Functional Genomics Analysis Of Economically Important Tramentioning
confidence: 99%
“…Curcin was isolated, cloned and sequenced [50, 54, 56]. Three contigs encoding amino acid sequences of curcin-like proteins were identified as highly similar to curcin [21].…”
Section: Functional Genomics Analysis Of Economically Important Tramentioning
confidence: 99%
See 1 more Smart Citation
“…A 654 bp fragment of a 5 0 flanking region preceding the curcin-L gene, designated CP2, was cloned from J. curcas and its expression was studied in transgenic tobacco via the expression of b-glucuronidase (GUS) gene. It was found that CP2 was leaf specific and could induce the expression of the reporter gene under stress conditions [37].…”
Section: Genes Associated With Abiotic Stress Tolerancementioning
confidence: 99%